Diet-Induced Obesity Does Not Alter Tigecycline Treatment Efficacy in Murine Lyme Disease - Pětrošová, Helena; Eshghi, Azad; Anjum, Zoha; Zlotnikov, Nataliya; Cameron, Caroline E.; Moriarty, Tara J. (Frontiers in Microbiology, 2017)
Obese individuals more frequently suffer from infections, as a result of increased susceptibility to a number of bacterial pathogens. Furthermore, obesity can alter antibiotic treatment efficacy due to changes in drug pharmacokinetics which can result in under-dosing. However, studies on the treatment of bacterial infections in the context of obesity are scarce. To address this research gap, we assessed efficacy of antibiotic treatment in diet-induced obese mice infected with the Lyme disease pathogen, Borrelia burgdorferi. Diet-induced obese C3H/HeN mice and normal-weight controls were infected with B. burgdorferi, and treated during the acute phase of infection with two doses of tigecycline, adjusted to the weights of diet-induced obese and normal-weight mice. Antibiotic treatment efficacy was assessed one month after the treatment by cultivating bacteria from tissues, measuring severity of Lyme carditis, and quantifying bacterial DNA clearance in ten tissues. In addition, B. burgdorferi-specific IgG production was monitored throughout the experiment. Tigecycline treatment was ineffective in reducing B. burgdorferi DNA copies in brain. However, diet-induced obesity did not affect antibiotic-dependent bacterial DNA clearance in any tissues, regardless of the tigecycline dose used for treatment. Production of B. burgdorferi-specific IgGs was delayed and attenuated in mock-treated diet-induced obese mice compared to mock-treated normal-weight animals, but did not differ among experimental groups following antibiotic treatment. No carditis or cultivatable B. burgdorferi were detected in any antibiotic-treated group. In conclusion, obesity was associated with attenuated and delayed humoral immune responses to B. burgdorferi, but did not affect efficacy of antibiotic treatment.